Proceedings of the 10th ACM/IEEE International Symposium on Empirical Software Engineering and Measurement 2016
DOI: 10.1145/2961111.2962598
|View full text |Cite
|
Sign up to set email alerts
|

Using Eye Tracking to Investigate Reading Patterns and Learning Styles of Software Requirement Inspectors to Enhance Inspection Team Outcome

Abstract: Background-Inspecting requirements and design artifacts to find faults saves rework effort significantly. While inspections are effective, their overall team performance rely on inspectors' ability to detect and report faults. Our previous research showed that individual inspectors have varying LSs (i.e., they vary in their ability to process information recorded in requirements document). To extend the results ofour previous LS research, this paper utilizes the concept ofeye tracking (to record eye movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Moreover, one-way ANOVA analyses carried out on fixation count and saccade count showed that there were significant differences among groups. Goswami et al [18] observed the gaze behavior of 13 participants with different learning styles when they tried to identify errors in a project document. Learning styles were assessed using the Felder and Silverman Index of Learning Style.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one-way ANOVA analyses carried out on fixation count and saccade count showed that there were significant differences among groups. Goswami et al [18] observed the gaze behavior of 13 participants with different learning styles when they tried to identify errors in a project document. Learning styles were assessed using the Felder and Silverman Index of Learning Style.…”
Section: Introductionmentioning
confidence: 99%